Audit Implementasi Clinical Pathway Diare Akut di Rumah Sakit Anak dan Bunda Harapan Kita Tahun 2016 - Sari, Desy Rachma (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2017)
This study aims to determine the implementation of clinical pathway of acute diarrhea with the audit process. This type of research is quantitative and qualitative by using operational research concept with document review method, data analysis and in-depth interview. The result of the research shows that the audit topic is the implementation of clinical pathway of acute diarrhea with the aim to assessing completeness of clinical pathway, compliance of primary responsible physician, primary responsible nurse, nutrition and pharmacy and assessing the length of stay with clinical pathway. Assessment standard used is the national standard that is KARS. The result of measurement showed that completeness of filling clinical pathway 25%, no variation on laboratory examination, nutrition and nursing care, but still found variation on additional drug 41%, and length of stay was 3.3 day. Some things that hospital need to do is developed policies related to clinical pathway, improve clinical pathway forms and socialization systems, make clinical pathway technical guidance, monitoring and evaluation systems, and reduce standards length of stay and discussion of variations in therapy.